Beyond pristine MOFs: carbon dioxide capture by metal–organic frameworks (MOFs)-derived porous carbon materials. Issue 3 (5th January 2017) - Kim, Hye Ryeon; Yoon, Tae-Ung; Kim, Seung-Ik; An, Jihyun; Bae, Youn-Sang; Lee, Chang Yeon
Abstract : Porous carbon materials were synthesized by pyrolysis of zinc-based MOFs. These materials exhibited superior CO2 capacities and better CO2 separation ability under humid conditions compared to those of the pristine MOFs. Abstract : Porous carbon materials were synthesized by simple pyrolysis of various zinc-containing MOFs. These materials exhibited superior CO2 capacities compared to those of the pristine MOFs. Moreover, the porous carbon materials, in contrast to their parent MOFs, showed an excellent CO2 separation ability under humid conditions.